Optimalisasi Penggunaan Model Pembelajaran Kooperatif Tipe Numbered Head Together untuk Meningkatkan Aktivitas Belajar Pendidikan Agama Islam dan Budi Pekerti Peserta Didik Kelas VI SDN 146/X Tanjung Solok pada Semester Ganjil Tahun Ajaran 2021/2022 - Yuliana Yuliana (Departement of Mathematics Education, 2022)
The purpose of this study was to obtain information and discuss optimizing the use of the numbered head together type of cooperative learning model to improve learning activities of Islamic religious education and character for the sixth grade students of SDN 146/X Tanjung Solok in the odd semester of the 2021/2022 academic year. This research is a classroom action research (CAR) which consists of two cycles, where each cycle consists of two meetings by following four stages in each cycle, namely planning, implementation, observation, and reflection. This research was carried out at SDN 146/X Tanjung Solok in the odd semester of the 2021/2022 academic year with 17 class VI students as the subject. data were collected through observation sheets, field notes, and documentation and analyzed using percentages and data reduction. Based on the results of the research and discussion that the author has done about cooperative learning with the Numbered Head Togehter type, it increases student learning activities in past religious education subjects and character in class VI SDN 146/X Tanjung Solok. It can be concluded that giving lessons through the Numbered Head Togehter cooperative learning model can increase student learning activities by replacing groups and giving additional points.